Moscow rules - Silva, Daniel, 1960- (New York : Signet/New American Library, 2009)
The death of a journalist leads Gabriel Allon to Russia, where he finds that, in terms of spycraft, even he has something to learn. He's playing by Moscow rules now. Ivan Kharkov, a former KGB colonel who built a global investment empire on the rubble of the Soviet Union, is an arms dealer and he is about to deliver Russia's most sophisticated weapons to al- Qaeda. Unless Allon can learn the time and place of the delivery, the world will see the deadliest terror attacks since 9/11and the clock is ticking fast.
Title also appears in Russian on t.p.
Keywords: Allon, Gabriel (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Intelligence officers -- Fiction; Military weapons -- Fiction; Moscow (Russia) -- Fiction; Spy stories; Suspense fiction